Peningkatan Nilai Ekonomis Limbah Tempurung Kelapa Menjadi Briket Sebagai Produk Unggulan Di Kabupaten Padang Pariaman - Armiati Armiati; Dessi Susanti; Andi Alatas; Rita Syofyan; Rose Rahmidani; M. Topit Hidayat; Fachri Irsan; Nelsa Onelfa (MALLOMO: Journal of Community Service, 2024)
Coconut is a plantation commodity in Padang Pariaman Regency that has experienced an increase in production during 2023. The waste from coconut shells can be further processed into a product with high economic value and even reach the export market, namely coconut charcoal briquettes. The purpose of this activity is to provide knowledge and skills about production, promotion, marketing, and financial management to the partners. The method used is community development through lectures, discussions, Q&A sessions, practical activities, and mentoring. The partners for this activity are the Sukses Bersama and Maju Makmur Business Groups, with 15 participants. The evaluation results show that 100% of the participants gave positive responses and answers to all questions asked about the training activities. The outcome of this service is significant for the participants to improve the quality of the briquette products, as well as marketing and financial management.